Effects of β-hydroxy-β-methylbutyrate supplementation on muscle mass and strength in onabotulinumtoxin type-A-injected and contralateral quadriceps femoris in rabbits - Rafael Fortuna; Andrew Sawatsky; John C. Fuller, Jr; Walter Herzog (Medical Journals Sweden, 2021)
Objective: To determine the effects of the leucine metabolite β-hydroxy-β-methylbutyrate (HMB) on strength, muscle mass, and contractile material in muscle wasting induced by onabotulinumtoxin type-A (BoNT-A) injection into the quadriceps femoris muscles of New Zealand white rabbits. Methods: A total of 21, female rabbits were divided into 3 groups (n=7, each). Group 1 (Control) received intramuscular injection of saline. Groups 2 and 3 received intramuscular injection of BoNT-A (3.5 units/kg), with group 3 receiving supplementation with HMB (120 mg/kg-BW/day). Muscle morphology, mass, and strength were assessed 8 weeks later in both injected and non-injected contralateral limbs. Results: Injected muscle strength of group 2 (BoNT-A) and group 3 (BoNT-A+HMB) was reduced by 63% and 60%, respectively, compared with Controls (p<0.0001). Strength in contralateral muscles of group 2 was reduced by 23% vs Controls (p<0.002), while in group 3, strength was similar to Controls. Muscle mass in the injected muscles of the BoNT-A and BoNT-A+HMB groups was significantly reduced, by 46% and 48%, respectively. Conclusion: While HMB did not prevent loss of muscle strength and mass in the BoNT-A-injected musculature, it prevented significant loss of contractile material in the injected musculature and strength loss in the contralateral non-injected musculature.